Bridging the Gap: A Systematic Literature Review on Performance Appraisal Interviews Using the PRISMA Framework - Karki, Sarala (SADGAMAYA, 2025)
This paper presents a comprehensive systematic review of performance appraisal interviews (PAIs) across diverse organizational contexts using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Analyzing 31 studies from JSTOR, Wiley Online Library, and ResearchGate, it identifies recurring challenges, practices, and strategies in PAIs. A critical research gap is highlighted: the scarcity of studies addressing PAIs in Nepal. The findings emphasize transparency, participatory methods, digital tools, and cultural adaptability. This paper proposes tailored frameworks to modernize Nepali institutions' practices.